Digital Supply Chain Management: An Analysis of Technology Integration and Optimization of Modern Inventory Systems - Yulie, Annisa Rizkyta; Aprilianz, Flowrent; Pazizi, Magdalena; Putri, Salwa Nabilah; Yusnaini, Yusnaini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid pace of digitalization is having a transformative impact on modern supply chain management, particularly in the implementation of Digital Supply Chain Management (DSCM). The integration of digital technologies such as integrated information systems, the Internet of Things (IoT), big data analytics, and cloud-based platforms—enables companies to enhance visibility, coordination, and efficiency in managing the flow of goods and information. This study aims to explain how the integration of technology in the digital supply chain can support the optimization of modern inventory systems and improve a company’s operational performance. This research was conducted using a systematic literature review approach, examining various relevant scientific publications related to the digital supply chain and inventory management. The findings indicate that the implementation of high-performance digital technologies significantly contributes to optimizing inventory planning accuracy, accelerating decision making processes, and minimizing the risks of overstocking or stockouts. Additionally, the use of digital technologies enables companies to monitor inventory in real-time and optimize their ability to respond to changes in market demand. Therefore, the implementation of Digital Supply Chain Management is a critical strategy for organizations to optimize modern inventory systems, drive operational efficiency, and strengthen the company’s competitive capabilities in the era of digital transformation.